2018
DOI: 10.1002/eat.22821
|View full text |Cite
|
Sign up to set email alerts
|

Cue reactivity, habituation, and eating in the absence of hunger in children with loss of control eating and attention‐deficit/hyperactivity disorder

Abstract: Desire to eat among children with comorbid LOC eating and ADHD was associated with overeating in the absence of hunger, which may contribute to excess weight gain. Delineation of the specific features of childhood LOC eating versus ADHD warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…ADHD has also been found to be significantly associated with eating disorders (EDs) (i.e., anorexia nervosa [AN], bulimia nervosa [BN], and binge eating disorder [BED]) [9]. In addition, ADHD is associated more generally with addictive-like eating behavior, even when no ED is diagnosed, notably loss of control overeating [10], binge eating (i.e., recurrent consumption of unusually large amounts of food during a discrete period of time while experiencing loss of control over food intake), and food addiction (FA) (i.e., addictive-like eating behaviors in relation to specific foods high in fat and/or refined carbohydrates, including craving, loss of control overeating, harm related to the behavior, and maintenance of the behavior despite negative consequences) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…ADHD has also been found to be significantly associated with eating disorders (EDs) (i.e., anorexia nervosa [AN], bulimia nervosa [BN], and binge eating disorder [BED]) [9]. In addition, ADHD is associated more generally with addictive-like eating behavior, even when no ED is diagnosed, notably loss of control overeating [10], binge eating (i.e., recurrent consumption of unusually large amounts of food during a discrete period of time while experiencing loss of control over food intake), and food addiction (FA) (i.e., addictive-like eating behaviors in relation to specific foods high in fat and/or refined carbohydrates, including craving, loss of control overeating, harm related to the behavior, and maintenance of the behavior despite negative consequences) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…According to one recent study (2018), children with ADHD may have less control while eating and thus consume more calories than healthy subjects. In addition, children diagnosed with ADHD may eat more food even when they are satiated compared to healthy subjects (14). Faster eating in children with ADHD, the inability to focus on hunger-satiety cycles, and the inability to perceive body stimuli may all lead to impaired eating-feeding patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The current study was part of the Swiss University Study of Nutrition (SUN), investigating psychological and food intake related characteristics of children with LOC-E compared to ADHD and healthy controls [3941]. Recruitment took place in 125 classes of 35 regular primary schools (3rd to 6th grade) in French and German speaking parts of Switzerland (Berne, Lausanne, Fribourg).…”
Section: Methodsmentioning
confidence: 99%
“…Parts of this study were reported in the doctoral dissertation of Daniela Dremmel. Several articles have been published based on the same sample that were however related to other research questions [3941]. The authors declare that they have no conflict of interest.…”
mentioning
confidence: 99%